John Locke and Agrarian Capitalism - Wood, Neal. (Berkeley : University of California Press, 1984)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1984.
Intro -- Contents -- Preface -- Principal Primary Sources and Abbreviations -- CHAPTER ONE. A Question of Method -- CHAPTER TWO. Locke's Interest in Husbandry -- CHAPTER THREE. The Context of Economic Ideas: 1668-92 -- CHAPTER FOUR. "Of Property" Reexamine -- CHAPTER FIVE. Consideration of an Opposing View -- CHAPTER SIX. The Unity of Locke's Thought -- CHAPTER SEVEN. Conclusion -- Notes -- Index
Description based upon print version of record.
JSTOR
Keywords: Locke, John, -- 1632-1704.; Locke, John, -- 1632-1704; Great Britain -- Economic conditions -- 17th century; Capitalism -- History -- 17th century; Grande-Bretagne -- Conditions économiques -- 17e siècle.; Capitalism; Economic history; Great Britain; 1600-1699; History